Cosmeceuticals in hyperpigmentary disorders - Subburaj Kiruthika; Jain Sejal; Vinay Keshavmurthy (Wolters Kluwer Medknow Publications, 2023)
Cosmeceuticals are hybrids between cosmetics and pharmaceuticals containing ingredients that modify the skin's functions and enhance its appearance. They are a bridge between drugs and cosmetics for minor skin ailments. The lack of proper regulatory standards for cosmeceuticals makes it very important for the dermatologists to educate the patient regarding their safety, or consequences of lack of knowledge thereof. In hyperpigmentation disorders, cosmeceuticals specifically target melanocytes and block the important regulatory steps in melanin synthesis, especially tyrosinase. The various agents include arbutin, bakuchiol, ferulic acid, kojic acid, licorice root extract, nicotinamide, plant extracts, resorcinol, retinol, sunscreens, thiamidol, and vitamin C. Plant extracts have minimal side-effects and are gaining popularity. They include aloe vera extract, cinnamic acid, coffeeberry, flavonoids, grape seed extract, green tea extracts, marine algae extract, mulberry extract, N-acetyl glucosamine, orchid extract, pycnogel, soy and umbelliferone. There is a requirement for large randomised controlled trials to establish their efficacy and adverse effects. Patient follow-up and compliance are the cornerstones of any skin therapy as any cosmeceutical use can produce gradual results when compared to conventional therapies. The PubMed database was searched using 'hyperpigmentation disorders' OR 'melasma' AND 'cosmeceuticals' as keywords. Abstracts were screened to include studies in the English language and those pertaining to the use of cosmeceuticals in hyperpigmentary disorders. In this review, we summarise the existing literature on the utility of cosmeceuticals in the treatment of hyperpigmentary diseases.